Status of Households Ducks and their Associated Factors under Scavenging System in a Southern Area of Bangladesh - Ghosh, S; Haider, N; Khan, MKI (International Journal of Natural Sciences, 2013)
This study was carried out to assess the status of household ducks and factors affects the productivity of ducks in Companiganj upazila under Noakhali district of Bangladesh. For this study the information was collected by direct interview using a questionnaire from 30 households. The study showed that duck rearing was mostly lead by the women (80%) and their level of education varied from primary (43%) to higher secondary (7%). The average farm size was found to be six and they were mostly local ducks (90%). Marshy lands were common (67%) to the surroundings of the duck habitats. Most of the farmers depended on natural feed sources (60%) while some provided supplementary feed (40%) for their ducks. As a supplementary feed, 27% of the farmers used rice polish and17% used a mixture of rice polish and boil rice. Duck started their first laying at 6 months of age and the mean egg production per duck per year was 114 ±16 no. The diseases were more common during winter (63%) than other seasons of the year. It was found that good egg production (> mean production) was associated with the regular use of anthelmintics, supplementary feed, presence of marshy land and regular treatment. Zending was found to be good egg producer in marshy area than other three native breeds of ducks. DOI: http://dx.doi.org/10.3329/ijns.v2i4.13288 International Journal of Natural Sciences (2012), 2(4) 108-111